Standards and standard setting and the post school curriculum - Young, Michael (Faculty of Education, University of the Free State, 2014)
This paper is concerned with the role of standards and standard setting in shaping the expansion of post school education in highly unequal society. It draws on an account of the debates and policies on standards in the UK from the 1980’s to today and the wider lessons that can be learned from them. It argues that relying on any type of standards on their own, independently of any consideration of curriculum, pedagogy and the distribtution of educational resources is doomed to failure. It concludes by linking the idea of higher stadards for all to Morrow’s concept of ‘epistemic access’.
Keywords: Standards; Standard setting; Post school education; Epistemic access